PENGEMBANGAN MEDIA SIDARA (KOLABORASI BUDAYA NUSANTARA) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR MATERI KERAGAMAN BUDAYA MASYARAKAT - Putri, Rosidatul Halim Najib; Wahyuningtyas, Neni (Jurnal Pendidikan Sultan Agung, 2025)
The low activeness of students is still often found in social studies learning. One of these problems is caused by the lack of use of innovative and contextual learning media. In order to overcome this problem, flashcard-based SIDARA (Kolaborasi Budaya Nusantara) learning media integrated with educational blogs containing cultural text readings, illustrative images of culture and interactive videos of Indonesian culture were developed. This research aims to produce flashcard-based SIDARA (Kolaborasi Budaya Nusantara) media combined with educational blogs to increase the learning activeness of class VII I students. The method used in this research is Reserch and Development with the ADDIE model. The results of the implementation of SIDARA learning media for students of class VII I SMP Negeri 10 Malang show that this media is very feasible to use in social studies learning. SIDARA media is effective in increasing students' learning activeness through observation, exploration and collaboration activities. This research is expected to be an innovative solution to support technology-based learning and facilitate diverse learning styles. Suggestions for future research are to expand SIDARA content to include more cultural elements from various regions in Indonesia.